A tecnologia da informação como agente de transformação do modelo de gestão: o caso DETRAN-RJ - Fleury, Newton Meyer (2001)
The aim of this dissertation is to study the relation between information technology (IT) and organizational management models by defining the manner in which IT can contribute to their transformation. This study is based on a theoretical reference framework which describes the evolution of the extent and functionality of the use of information technology as a tool for business management, with especial emphasis on the development of the capacity of data and Internet communication networks to establish connections among people, companies and communities. The theoretical reference framework also presents different approaches on how to enhance alignment between information technology and organizational management models, taking into account formal aspects related to the detailing of organizational and technical requisites and social implications concerning the introduction of innovations in previously established cultural environments. The study also contains an empirical section based on a case study on the State of Rio de Janeiro Traffic Department (DETRAN-RJ) in which some of the concepts and methods of approach described in the theoretical reference framework were employed. Keywords: Logistic Services Chain, E-Government, Management Model, Organizational Network, Information Technology